Surface-enhanced Raman scattering in cancer detection and imaging - Vendrell, Marc; Maiti, Kaustabh Kumar; Dhaliwal, Kevin; Chang, Young-Tae (Trends in biotechnology (Regular ed.), 2013)
► Assays to quantify cancer biomarkers with high sensitivity and low sample volumes. ► Imaging of cancer cells, tissues, and small animals with multiplexed capabilities. ► Multimodal SERS probes and their potential for clinical translation. Technologies that use surface-enhanced Raman scattering (SERS) have experienced significant growth in biomedical research during the past 4 years. In this review we summarize the progress in SERS for cancer diagnostics, including multiplexed detection and identification of new biomarkers, single-nucleotide polymorphisms, and circulating tumor cells. SERS is also used as a non-invasive tool for cancer imaging with immunoSERS microscopy, histological analysis of biopsies, and in vivo detection of tumors. We discuss the future of SERS probes compatible with multiple imaging modalities and their potential for clinical translation (e.g., endoscope-based and intraoperative imaging as tools for surgical guidance). Moreover, we highlight the potential of SERS agents for targeted drug delivery and photothermal therapy.